DEVELOPMENT OF INSTANT PUMPKIN-FINGERROOT DRINK POWDER AND ITS SHELF LIFE MODELING - Srisuk, Narakorn; Jirasatid, Sani (Life Sciences and Environment Journal, 2023)
The objective of the present study was to develop a healthy instant pumpkin-fingerroot drink powder (IPFDP) using freeze-drying technique and establish the kinetic models to predict its shelf life based on two major indices viz., water activity (aw) and sensory quality. Firstly, freeze-dried instant drink powder in different ratios of pumpkin and fingerroot (50:50, 70:30, 80:20 90:10, 100:0 and 0:100 (w/w)) were prepared and the qualities were investigated. It was found that the aw of all IPFDP formulas were within the range 0.33-0.35. The instant drink powder prepared from pumpkin and fingerroot in the ratio of 80:20 (formula C) contained significant yields of β-carotene (6.25 µg/g) and total phenolic content (206.56 mg GAE/g) and also possessed the strongest 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant activity (39.15%). This formula also exhibited the highest score of all sensory attributes (7.56-7.98 scores). Based on these results, formula C was selected for consequent storage. The solid samples were packed in the aluminium foil bags under atmospheric pressure and then kept at temperatures of 4 C, room temperature (32 C) and 45 C for 70 days. IPFDP underwent increasing aw values and color changes (L*, a*, b*, total color difference and browning index) causing a lower sensorial consumer acceptance with the increases in storage period and temperature.